SELF ASSESSMENT IN WRITING SKILL OF INTROVERTED STUDENTS - Sofeny, Daniar (E-Link Journal, 2019)
Self assessment is one of parts in assessment process. This process helps the students evaluate their own work and learning process. This study try to implement one of self assessments, namely Type Token Ratio (TTR). It calculates word repetition by deviding the total number of words in a text (tokens) by the number of individual words. This self assessment will be used to only one type of personalities, namely introverted students. The aims of the study are describing the types of token that most used by the introverted students, describing the types of token rarely used by the introverted students, and describing the introverted students opinion about Type Token Ratio (TTR) for their writing. The descriptive qualitative method was implemented in this study. the sources of the data were taken from twenty students of first semester in English Educational Program of UNISDA Lamongan. The findings showed that types of token most used by the introverted students are: nouns appear 466 times, verbs appear 266 times, pronouns appear 266 times and prepositions appear 251 times. Whereas, they rarey used: adverbs appears 171 times, determiners appears 159 times, conjunctions appear 123 times, adjectives appear 94 times and interjections appear 7 times. Based on the result, it can be concluded that the introverted students most often use noun and most rarely use interjection in their writing. Almost all of students think that TTR is good and help them to measure their vocabulary variety.Key words: Self Assessment, Writing Skill, Introverted